The phylum Cnidaria: A review of phylogenetic patterns and diversity 300 years after Linnaeus* - Daly, Marymegan; Brugler, Mercer R.; Cartwright, Paulyn; Collins, Allen G.; Dawson, Michael N.; Fautin, Daphne G.; France, Scott C.; Mcfadden, Catherine S.; Opresko, Dennis M.; Rodriguez, Estefania; Romano, Sandra L.; Stake, Joel L. (Zootaxa, 2007)
Systema Naturae includes representatives of every major lineage of the animal phylum Cnidaria.  However, Linnaeus did not classify the members of the phylum as is now done, and the diversity of the group is not well represented.  We contrast the Linnaean perspective on cnidarian diversity with the modern, phylogenetic perspective.  For each order, we detail diversity at the family level, providing phylogenetic context where possible.